(untitled) - F Moriarty (London, 1990)
The book starts with a basic introduction to the principles of community ecology. Then, it discusses the chemistry or toxicology with biological background necessary to see pollutants in environmental context. It also discusses the effects of pollutants and methods of monitoring polution
Keywords: environment - pollution,environmental policy,environmental protection